GEOLOGICAL STRUCTURE, MINERALOGY, AND GENESIS OF THE ZHELANNOE QUARTZ DEPOSIT (PRIPOLYARNYI URALS, RUSSIA) - Repina S.A. (My University, 2001)
The Zhelannoe vein quartz and rock crystal deposit are unique in their geological structure, scale and high quality of ore mineralization and mineral product. The economic ores of the deposit are enclosed in monomineralic quartzite-sandstones of Early Ordovician age. At the base of giant quartz veins, almost monomineralic sericitic rock bodies (sericitoliths) containing large amounts of rutile, zircon, and REE minerals occur. The origin of sericitoliths is not metasomatic according to some geological and mineralogical evidence. A model of synchronous deposition of the sericitoliths and vein quartz is proposed based on detailed geological, mineralogical, and geochemical study of the deposit. The model implies a liquation of the hydrothermal solution and consequent sedimentation of some of mineral substance in tectonic cavities. The consequent crystal formation was not accompanied by additional introduction of hydrothermal solution, but was caused by decreasing pressure in reopened cavities and by reactions between minerals and undersaturated solution that was residual after deposition of the vein quartz and sericitoliths. The economic concentration of rutile, zircon, and REE minerals and the high concentrations of Cr, W, Th, and Nb are determined for the first time in the sericitoliths.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская